2022
DOI: 10.3389/fimmu.2022.811378
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Microcin J25 Exerts Strong Antibacterial, Anti-Inflammatory Activities, Low Cytotoxicity Without Increasing Drug-Resistance to Bacteria Target

Abstract: Multidrug resistant (MDR) bacterial infection has emerged, raising concerns about untreatable infections, and posing the highest health risks. Antimicrobial peptides (AMPs) are thought to be the best remedy for this problem. Here, we showed biosynthetic microcin J25 (MccJ25) exhibited excellent bactericidal activity against standard and clinically relevant veterinary MDR strains with high stability, no cytotoxicity, and no increase in drug resistance. Analysis of antimicrobial mechanism possessed by sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Indeed, MccJ25, which is produced by bacteria of the family Enterobacteriaceae and contributes to competition in the gut has a narrow spectrum of antibacterial activity. It is reportedly bactericidal to Gram-negative species including E. coli , Salmonella and Shigella ( Rintoul et al, 2001 ; Yu et al, 2022 ). Highly purified MccJ25 was recently shown to exert efficient bactericidal activity in vitro against clinically relevant veterinary multidrug-resistant strains and to decrease inflammation in a mouse E. coli infection model ( Yu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MccJ25, which is produced by bacteria of the family Enterobacteriaceae and contributes to competition in the gut has a narrow spectrum of antibacterial activity. It is reportedly bactericidal to Gram-negative species including E. coli , Salmonella and Shigella ( Rintoul et al, 2001 ; Yu et al, 2022 ). Highly purified MccJ25 was recently shown to exert efficient bactericidal activity in vitro against clinically relevant veterinary multidrug-resistant strains and to decrease inflammation in a mouse E. coli infection model ( Yu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The thermal activity of Spgillcin 177–189 against S. aureus and P. aeruginosa was evaluated based on a previous report ( Yu et al., 2022 ) with some modifications. Briefly, a logarithmic-growth phase of S. aureus and P. aeruginosa was harvested and diluted to approximately 1 × 10 6 CFU ml -1 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, Spgillcin 177-189 maintained its antimicrobial activity and was stable even with changing temperature and salt conditions. A steady-state condition may be a prerequisite for the further application of Spgillcin 177-189 , as it has been reported previously that the AMP Microcin J25 can effectively kill MDR E. coli even during fluctuating pH and temperature (Yu et al, 2022). Cytotoxicity is also a primary drawback to the clinical application of peptide drugs (van der Kraan et al, 2004), also restricting the topical utilization of AMPs.…”
Section: B a Figure 11mentioning
confidence: 99%
“…Studies demonstrating regulation of microbial communities using purified microcin have emerged only in the last few years, probably due to improvements in the purification process. The majority of these have examined purified MccJ25 treatment [184, 187–191], though one study used purified MccC [185]. With MccJ25, there has been an emphasis on investigating its anti-inflammatory properties and improvements in intestinal barrier function, which are presumably due, at least in part, to effects on the microbial community and/or elimination of specific pathogens [184, 187, 190, 191].…”
Section: Ecological Roles Of Microcinsmentioning
confidence: 99%
“…The majority of these have examined purified MccJ25 treatment [184, 187–191], though one study used purified MccC [185]. With MccJ25, there has been an emphasis on investigating its anti-inflammatory properties and improvements in intestinal barrier function, which are presumably due, at least in part, to effects on the microbial community and/or elimination of specific pathogens [184, 187, 190, 191]. Several of these studies have found increases in the abundance of specific taxonomic groups (e.g.…”
Section: Ecological Roles Of Microcinsmentioning
confidence: 99%